2013
DOI: 10.1093/eurjhf/hfs215
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan in acute heart failure following primary percutaneous coronary intervention‐treated acute ST‐elevation myocardial infarction. Results from the LEAF trial: a randomized, placebo‐controlled study

Abstract: AimsThe calcium sensitizer levosimendan may counteract stunning after reperfusion of ischaemic myocardium, but no randomized placebo-controlled trials exist regarding its use in PCI-treated ST-segment elevation infarction (STEMI). We evaluated the efficacy and safety of levosimendan in patients with a primary PCI-treated STEMI complicated by symptomatic heart failure (HF). Methods and resultsA total of 61 patients developing clinical signs of HF within 48 h after a primary PCI-treated STEMI (including cardioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 34 publications
(63 reference statements)
1
89
0
7
Order By: Relevance
“…This study also found that levosimendan reduced the risk of worsening heart failure and death in patients with LV failure complicated by AMI. In the LEAF study [23], more episodes of hypotension occurred during the levosimendan infusion when compared to placebo treatment, but there was no significant difference in blood pressure at the end of the infusion when comparing the 2 groups. These small studies [11,12,13,14,23] indicate that levosimendan is a safe drug for use in AMI and does not increase the incidence of myocardial ischemia, mortality or serious arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that levosimendan reduced the risk of worsening heart failure and death in patients with LV failure complicated by AMI. In the LEAF study [23], more episodes of hypotension occurred during the levosimendan infusion when compared to placebo treatment, but there was no significant difference in blood pressure at the end of the infusion when comparing the 2 groups. These small studies [11,12,13,14,23] indicate that levosimendan is a safe drug for use in AMI and does not increase the incidence of myocardial ischemia, mortality or serious arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…The patient population and study design in the LEAF trial have previously been described in detail 19. Briefly, 61 patients with PCI‐treated STEMI who (i) had successful opening of the occluded coronary artery, (ii) had decreased wall motion in at least 3 of 16 segments of the left ventricle evaluated by echocardiography, and (iii) developed clinical signs of HF within 48 h (range: 14–33 h) following PCI were randomized to treatment with the calcium sensitizer levosimendan or placebo 19.…”
Section: Methodsmentioning
confidence: 99%
“…The present study is a post hoc study of the LEAF (LEvosimendan in Acute heart Failure following myocardial infarction) trial,19 an interventional study on patients developing HF within 48 h following PCI‐treated STEMI. We hypothesized that enhanced complement activation could be a hallmark of acute HF in this patient group and may discriminate between HF with or without cardiogenic shock.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials and their meta-analyses have reported its clinical efficacy, including improved cardiac performance, rapid symptom relief, reduced hospital stays and better survival in patients with ADHF [28,29]. It also increases renal blood flow and glomerular filtration rate as other positive inotropes do [30].…”
Section: Established Treatment Strategiesmentioning
confidence: 99%